Identification of Mineralization Zones Using Geoelectrical Methods Self-Potential (Sp) in Pemali Village Bangka Regency - Angrainy, Renata; Hariyono, Muhammad Budi; Mariana, Susi; Widyaningrum, Yekti (Jurnal Riset Fisika Indonesia, 2021)
Bangka Belitung as an area that has a lot of potential natural mineral resources, especially tin minerals, this tin mineral potential can be utilized for industrial and non-industrial purposes. Utilization of these minerals can be done by way of exploration, exploration of mineral distribution can be done directly in the field using geophysical methods. In this study the method used is the geoelectric method of self-potential (Sp) fixed base configuration. Data acquisition was carried out in two research sample areas, namely, region 1 and region 2 with a distance between the porouspot electrodes as far as 5 m. Data retrieval on the rover was carried out at each point of the trajectory, three times the data was taken with an interval of 30 seconds, while the retrieval at the base in region 1 was carried out every 3 minutes while in region 2 it was carried out every 1 minute. The research is focused on identifying the distribution of mineral zones below the surface. The results of the study are in the form of a contour map that describes the distribution pattern of potential difference anomalies (Sp) and a topographical anomaly map at the research location, which will later be interpreted to determine the direction of the distribution of minerals below the surface of the study site.